Relationship Between Environmental Concern, Green Perceived Value and Green Purchase Behaviour: The Moderating Role of Price Consciousness - Van Hoang, Dinh; Le Thanh, Tung (Organizations and Markets in Emerging Economies, 2024)
Growing environmental concerns influence consumer buying decisions and behaviours. This study investigates the factors that affect the green purchase behaviours of Generation Z consumers in Vietnam. Employing the value–attitude–behaviour (VAB) framework, the study examines the intricacies of green consumption behaviour. Study data were collected through an online questionnaire from 283 young Vietnamese consumers who frequently purchase green products. We performed the quantitative analysis by the partial least squares structural equation modelling (PLS-SEM) and found that price consciousness and attitude towards green products directly influence green purchase behaviour. Environmental concern and green perceived value indirectly influence green purchase behaviour through consumer attitude. Furthermore, the influence of price consciousness enhances the relationship between attitude and green purchase behaviour. These findings provide valuable implications for managers aiming to attract young, environmentally conscious consumers and promote green consumption behaviours.
Keywords: customer attitude; environmental concern; green perceived value; green purchase behaviour; price consciousness